Work and Livelihoods History, Ethnography and Models in Times of Crisis - Narotzky, Susana; Goddard, Victoria (Routledge Studies in Anthropology, 2017)
Winner of the Society for the Anthropology of Work book prize 2017 This volume presents a global range of ethnographic case studies to explore the ways in which - in the context of the restructuring of industrial work, the ongoing financial crisis, and the surge in unemployment and precarious employment - local and global actors engage with complex social processes and devise ideological, political, and economic responses to them. It shows how the reorganization and re-signification of work, notably shifts in the perception and valorization of work, affect domestic and community arrangements and shape the conditions of life of workers and their families.